2014
DOI: 10.4236/ajps.2014.53038
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulatory Effects of the Antimicrobial Agents Bavistin, Cefotaxime and Kanamycin on <i>In Vitro</i> Plant Regeneration of <i>Centella asiatica</i> (L.)—An Important Antijaundice Medicinal Plant

Abstract: Antimicrobial agents such as bavistin, cefotaxime and kanamycin were evaluated for their effects on the rapid shoot regeneration from nodal explants of Centella asiatica (L.). Filter sterilized bavistin (250 mg/L) was augmented alone and in combination with cytokinins such as BAP and TDZ into the media to trace the effect on regeneration. On this basis, the potential use of bavistin (150 mg/L) along with BAP (2.0 mg/L) was evaluated which showed the maximum shoot number (6.6) and shoot length (4.4 cm) respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…This shoot regeneration promoting activity of BVN was due to an increase in the biosynthesis of endogenous cytokinin within the culture explants. Since BVN is a broad spectrum fungicide it also eliminates fungi contaminating cultures (Panathula et al 2014). Similar observations were made in several other medicinal plants which were discussed in the light of stronger cytokinin like activity of BVN that have the resemblance of its molecular structure with kinetin, adenine and cytokinin.…”
Section: Resultssupporting
confidence: 64%
“…This shoot regeneration promoting activity of BVN was due to an increase in the biosynthesis of endogenous cytokinin within the culture explants. Since BVN is a broad spectrum fungicide it also eliminates fungi contaminating cultures (Panathula et al 2014). Similar observations were made in several other medicinal plants which were discussed in the light of stronger cytokinin like activity of BVN that have the resemblance of its molecular structure with kinetin, adenine and cytokinin.…”
Section: Resultssupporting
confidence: 64%
“…When microspores were cultivated in a medium without added antibiotics, developmental scenarios observed in the Petri dishes were as follows: (a) active bacterial growth accompanied by destruction of microspores (Figure 1b), the medium appeared turbid at five days ( Figure 2b); (b) weak bacterial growth seemingly due to weak phytotoxic effect, microspore embryo formation was still observed, although inhibited and reduced in amount ( Figure 3a); and (c) normal microspore embryo development in large amounts (Figure 3b). Multiple studies in different cultures demonstrated that antibiotics can both inhibit the growth and development of explants and cells and induce their regeneration [14][15][16][17][18][19][20]. It is assumed the stimulating effect is due to the auxin-like structure of β-lactam antibiotics that enables them to imitate the effect of plant hormones [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies in different cultures demonstrated that antibiotics can both inhibit the growth and development of explants and cells and induce their regeneration [14][15][16][17][18][19][20]. It is assumed the stimulating Plants 2020, 9, 489 2 of 10 effect is due to the auxin-like structure of β-lactam antibiotics that enables them to imitate the effect of plant hormones [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid higher contamination rates from these tissues, we evaluated a range of decontamination methods. Following reports of the addition of fungicides to tissue culture media to reduce fungal contamination (Nagy et al, 2005 ; Panathula et al, 2014 ), we added captan at 0.02 g/L, but it did not show any effect. We also tested a widely used broad spectrum product, Plant Presrvative Mixture™ (PPM; Plant Cell Technology, Washington, DC, United States), which reduced initial contamination in tissue culture but not beyond 2 weeks.…”
Section: Discussionmentioning
confidence: 99%